Multistate tuning of third harmonic generation in Fano-resonant hybrid dielectric metasurfaces - Abdelraouf, Omar A. M. (2022)
Hybrid dielectric metasurfaces have emerged as a promising approach to enhancing near field confinement and thus high optical nonlinearity by utilizing low loss dielectric rather than relatively high loss metallic resonators. A wider range of applications can be realized if more design dimensions can be provided from material and fabrication perspectives to allow dynamic control of light. Here, tunable third harmonic generation (THG) via hybrid metasurfaces with phase change material Ge₂Sb₂Te₅ (GST) deposited on top of amorphous silicon metasurfaces is demonstrated. Fano resonance is excited to confine the incident light inside the hybrid metasurfaces, and an experimental quality factor (Q-factor ≈ 125) is achieved at the fundamental pump wavelength around 1210 nm. Not only the switching between a turn-on state of Fano resonance in the amorphous state of GST and a turn-off state in its crystalline state are demonstrated, but also gradual multistate tuning of THG emission at its intermediate states. A high THG conversion efficiency of η = 2.9 × 10⁻⁶% is achieved, which is 32 times more than that of a GST-based Fabry–Pèrot cavity under a similar pump laser power. Experimental results show the potential of exploring GST-based hybrid dielectric metasurfaces for tunable nonlinear optical devices.